U.S. Seismic Steel Codes - Popov, Egor P. (Engineering Journal, 1991)
Major changes and recommendations for the seismic design of steel buildings were recently introduced into several U.S. design codes and specifications. Many of these changes deal primarily with material and detailing requirements. However, these problems cannot be separated from the underlying issues of lateral seismic loads. Therefore in this paper a broader point of view is adopted, and a brief discussion of relevant findings from seismology and geotechnical engineering is presented first. A general discussion of structural code developments and the relationships among the lateral load requirements in different codes follows. Specific issues pertaining to the seismic design of structures are then brought in. Limitations of the currently dominant elastic methods of analysis and design for seismic resistant structures are critically examined. The paper concludes with suggestions for future research.